Optimal Parochialism: The Dynamics of Trust and Exclusion in Networks - Samuel Bowles; Herbert Gintis (University of Massachusetts, Department of Economics, 2000)
Networks such as ethnic credit associations, close-knit residential neighborhoods, 'old boy' networks, and ethnically linked businesses play an important role in economic life but have been little studied by economists. These networks are often supported by cultural distinctions between insiders and outsiders and engage in exclusionary practices which we call parochialism. We provide an economic analysis of parochial networks in which the losses incurred by not trading with outsiders are offset by an enhanced ability to enforce informal contracts by fostering trust among insiders. We first model one-shot social interactions among self-regarding agents, demonstrating that trust (i.e., cooperating without using information about one's trading partner) is a best response in a mixed-strategy Nash equilibrium if the quality of information about one's partner is sufficiently high. We show that since larger networks have lower quality information about specific individuals and greater trading opportunities, there may be an optimal (payoff-maximizing) network size. We then model the growth and decline of networks, as well as their equilibrium size and number. We show that in the absence of parochialism, networks may not exist, and the appropriate level of parochialism may implement an optimal network size. Finally, we explore the welfare implications and reasons for the evolutionary success of exclusion on parochial and other grounds.
Keywords: 330